Surfactant protein-A nanobody-conjugated liposomes loaded with methylprednisolone increase lung-targeting specificity and therapeutic effect for acute lung injury - Nan Li; Dong Weng; Shan-Mei Wang; Yuan Zhang; Shan-Shan Chen; Zhao-Fang Yin; Jiali Zhai; Judy Scoble; Charlotte C. Williams; Tao Chen; Hui Qiu; Qin Wu; et al. (Taylor & Francis Group, 2017)
The advent of nanomedicine requires novel delivery vehicles to actively target their site of action. Here, we demonstrate the development of lung-targeting drug-loaded liposomes and their efficacy, specificity and safety. Our study focuses on glucocorticoids methylprednisolone (MPS), a commonly used drug to treat lung injuries. The steroidal molecule was loaded into functionalized nano-sterically stabilized unilamellar liposomes (NSSLs). Targeting functionality was performed through conjugation of surfactant protein A (SPANb) nanobodies to form MPS-NSSLs-SPANb. MPS-NSSLs-SPANb exhibited good size distribution, morphology, and encapsulation efficiency. Animal experiments demonstrated the high specificity of MPS-NSSLs-SPANb to the lung. Treatment with MPS-NSSLs-SPANb reduced the levels of TNF-α, IL-8, and TGF-β1 in rat bronchoalveolar lavage fluid and the expression of NK-κB in the lung tissues, thereby alleviating lung injuries and increasing rat survival. The nanobody functionalized nanoparticles demonstrate superior performance to treat lung injury when compared to that of antibody functionalized systems.